IMPLEMENTING KWL STRATEGY WITH PICTURES TO IMPROVE STUDENTS’ READING COMPREHENSION: AN ONLINE SETTING IN COVID-19 PANDEMIC - Ni Luh Made Sri Parwati; I Gde Putu Agus Pramerta (Academic Journal on English Studies (AJOES), 2021)
The study aimed at figuring out students' reading comprehension after treating with KWLstrategy and pictures as the media. It was conducted to the seventh-grade students of SMPN 7Mengwi in the academic year 2020/2021 with Google Classroom and WhatsApp: it was setonline in two cycles. because of Covid-19 pandemic. Based on the pre-test, it seemed that theproblems are in finding general information, specific information, textual meaning, and textualreference. The data were obtained by giving pre-test and post-test in each cycle. The subjects'mean score in the pre-test, post-test 1 and post-test 2 were improving from 51.21 to 63.28 incycle I and 80.46 in cycle II. It showed improvements concerning on their readingcomprehension. Furthermore, there were positive responses on the implementation of thestrategy. Hence, this study proved that reading comprehension could be improved throughKWL strategy with pictures.